Far from the madding crowd: Tolerance toward human disturbance shapes distribution and connectivity patterns of closely related Martes spp. Issue 3 (7th April 2019) - Balestrieri, Alessandro; Mori, Emiliano; Menchetti, Mattia; Ruiz‐González, Aritz; Milanesi, Pietro
Abstract: To assess niche overlap between the most similar European sympatric carnivores, the pine marten Martes martes and stone marten Martes foina, and outline their potential distributions and connectivity corridors in Central Italy, we applied a multivariate kernel density procedure which allowed to assess both species' ecological hypervolumes based on a set of 16 environmental predictors and used the resulting probability of occurrence map as a resistance surface in electrical circuit theory‐based models. Distance to watercourses and percent cover of deciduous forest and shrubland were the most relevant factors shaping pine marten ecological niche, while stone marten distribution was mainly shaped by human population density and cover of both human settlements and deciduous forest. Overlap between the hypervolumes of the two martens was low‐to‐moderate, while, on average, landscape connectivity was higher for the stone marten. The inclusion in the models of human disturbance‐related variables enabled to define a possible mechanism driving habitat partitioning in human‐altered landscapes. Based on our results, increasing human density and urbanization of European lowland and hilly landscapes are expected to represent a greater threat to the pine marten than the stone marten. Abstract : We assessed the ecological hypervolumes of the most similar European sympatric carnivores, the pine marten Martes martes and stone marten Martes foina . Overlap between the hypervolumes of the two martens was low‐to‐moderate, while landscape connectivity was higher for the stone marten. We pointed out the major role played by each species' tolerance toward human disturbance in shaping their relative patterns of distribution.